The Draft EU–MERCOSUR Agreement Drawing the Dividing Line Between Policy Cooperation and Trade - Nicolas de Sadeleer (European Journal of Risk Regulation)
The aim of this note is to shed some light on the “agreement in principle” concluded on 6 December in the light of the division of competences between the different EU institutions and the Member States. Whilst classification as an “agreement in principle” might initially appear to be primarily procedural in nature, the implications of its conclusion by the EU go beyond merely procedural issues. In effect, it touches on sensitive issues concerning the institutional balance between the European Commission, the Council of Ministers, the European Parliament and the Member States both within current negotiations and also in relation to the conclusion of a treaty with the MERCOSUR states. The possibility of splitting the trade limb from the political limb of a forthcoming association agreement is also addressed.